Tuning the bandgap of m-ZrO2 by incorporation of copper nanoparticles into visible region for the treatment of organic pollutants. (March 2020) - Singh, Harish; Sunaina,; Yadav, Krishna Kumar; Bajpai, Vaibhav Kumar; Jha, Menaka
Graphical abstract: Synthesis of Cu-ZrO2 photocatalyst for efficient removal of organic pollutant under visible light illumination Highlights: Bandgap tuning of pure m-ZrO2 has been done by incorporation of copper nanoparticles. Cu-ZrO2 nanocomposites were prepared by chemical reduction method in glycolic medium. The Cu-ZrO2 composite shows good photocatalytic activity for Methylene blue degradation. Photocatalytic mechanism of Cu-ZrO2 for Methylene blue dye degradation was studied by adding scavengers into the system. Abstract: In the present study, a low-temperature process for the stabilization of Cu-ZrO2 nanocomposite has been designed. The synthesis of m-ZrO2 has been done via hydrothermal route followed by decoration of copper onto m-ZrO2 surface by chemical reduction of copper salt in ethylene glycol. The optical study of the Cu-ZrO2 nanocomposites shows that, as the concentration of copper increases, the bandgap of the nanocomposite decreases. Among the series of synthesized nanocomposites of Cu-ZrO2, the nanocomposite having 1:4  molar ratio of Cu: ZrO2 shows the excellent photo-degradation efficacy (degradation efficiency ∼94 %) in the visible light because of efficient charge separation as confirmed by spectroscopic techniques as well as kelvin probe force microscopic studies.